Low myoglobin concentration in skeletal muscle of elite cyclists is associated with low mRNA expression levels - Jacobs, N.; Mos, D.; Bloemers, F. W.; van der Laarse, W. J.; Jaspers, R. T.; van der Zwaard, S. (European Journal of Applied Physiology, 2023)
Myoglobin is essential for oxygen transport to the muscle fibers. However, measurements of myoglobin (Mb) protein concentrations within individual human muscle fibers are scarce. Recent observations have revealed surprisingly low Mb concentrations in elite cyclists, however it remains unclear whether this relates to Mb translation, transcription and/or myonuclear content. The aim was to compare Mb concentration, Mb messenger RNA (mRNA) expression levels and myonuclear content within muscle fibers of these elite cyclists with those of physically-active controls. Muscle biopsies were obtained from m. vastus lateralis in 29 cyclists and 20 physically-active subjects. Mb concentration was determined by peroxidase staining for both type I and type II fibers, Mb mRNA expression level was determined by quantitative PCR and myonuclear domain size (MDS) was obtained by immunofluorescence staining. Average Mb concentrations (mean ± SD: 0.38 ± 0.04 mM vs. 0.48 ± 0.19 mM; P = 0.014) and Mb mRNA expression levels (0.067 ± 0.019 vs. 0.088 ± 0.027; P = 0.002) were lower in cyclists compared to controls. In contrast, MDS and total RNA per mg muscle were not different between groups. Interestingly, in cyclists compared to controls, Mb concentration was only lower for type I fibers (P < 0.001), but not for type II fibers (P > 0.05). In conclusion, the lower Mb concentration in muscle fibers of elite cyclists is partly explained by lower Mb mRNA expression levels per myonucleus and not by a lower myonuclear content. It remains to be determined whether cyclists may benefit from strategies that upregulate Mb mRNA expression levels, particularly in type I fibers, to enhance their oxygen supply.